'Affective encounters': live intermedial spaces in sites of trauma. Issue 3 (2nd July 2016) - Scott, Jo
ABSTRACT: This article addresses live intermediality as a tool for creative learning in the context of workshops carried out with young people in the town of Terezin, in the Czech Republic, site of the Nazi concentration camp, Theresienstadt. Live intermediality, as a mode of live media practice, involves the real time mixing and merging of sound, image, text and body, with a particular focus on the intersection between digital and physical modes. Employing both a written exposition and intermedial materials, in the form of a 'video-text', the article reflects on, positions and opens up this practice, specifically in relation to the 'affective encounters' [Bennett, Jill.2005 . Empathic Vision: Affect, Trauma and Contemporary Art . Stanford, CA: Stanford University Press., 37] it generated between the workshop participants and the 'traces of past people and events' [Simon, Roger I., Sharon Rosenberg, and Claudia Eppert, eds. 2000. Between Hope and Despair: Pedagogy and the Remembrance of Historical Trauma . Oxford: Rowman and Littlefield, 7] in Terezin. In doing so, I propose that live intermediality, with its emphasis on the real time mixing of diverse elements and responses, has a particular capacity to generate creative practice which is 'transactive' (Bennett 2005, 5) and where affect 'flow[s] through bodies and spaces, rather than residing within a single subject' [Bennett, Jill.2005 . Empathic Vision: Affect, Trauma and Contemporary Art . Stanford, CA: Stanford University Press, 13]. With its focus on 'the act of doing as the generator of meaning' [Bryon, Experience. 2014. Integrative Performance: Practice and Theory for the Interdisciplinary Performer . London: Routledge, 214], this practice prompted 'affective encounters' with aspects of the past trauma of Terezin, through the participants' live intermedial creation, in and in response to the present site.